Assessing the gene silencing potential of AuNP-based approaches on conventional 2D cell culture versus 3D tumor spheroid - Oliveira, Beatriz B.; Fernandes, Alexandra R.; Baptista, Pedro Viana (Frontiers in Bioengineering and Biotechnology, 2024)
Three-dimensional (3D) cell culture using tumor spheroids provides a crucial platform for replicating tissue microenvironments. However, effective gene modulation via nanoparticle-based transfection remains a challenge, often facing delivery hurdles. Gold nanoparticles (AuNPs) with their tailored synthesis and biocompatibility, have shown promising results in two-dimensional (2D) cultures, nevertheless, they still require a comprehensive evaluation before they can reach its full potential on 3D models. While 2D cultures offer simplicity and affordability, they lack physiological fidelity. In contrast, 3D spheroids better capture in vivo conditions, enabling the study of cell interactions and nutrient distribution. These models are essential for investigating cancer behavior, drug responses, and developmental processes. Nevertheless, transitioning from 2D to 3D models demands an understanding of altered internalization mechanisms and microenvironmental influences. This study assessed ASO-AuNP conjugates for silencing the c-MYC oncogene in 2D cultures and 3D tumor spheroids, revealing distinctions in gene silencing efficiency and highlighting the microenvironment's impact on AuNPmediated gene modulation. Herein, we demonstrate that increasing the number of AuNPs per cell by 2.6 times, when transitioning from a 2D cell model to a 3D spheroid, allows to attain similar silencing efficiencies. Such insights advance the development of targeted gene therapies within intricate tissuelike contexts.